The Purposive Transformation of Corporate Law. (16th March 2022) - Kershaw, David; Schuster, Edmund
Abstract: What is the purpose of a corporation? This fundamental question is as old as corporate law itself, and traditionally it is asked with reference to the ultimate beneficiaries of a corporation's activities. Modern management theory and the current technology-driven transformation of the economy, however, have breathed new life into the question about corporate purpose. Here, purpose is understood as an animated mission-purpose articulation of the reason for a corporation's existence; an aspirational idea about its existence that has the capacity to bond internal and external stakeholders to the company, inspiring innovation, productivity, and customer loyalty. This understanding of corporate purpose offers a pathway to a more inclusive and interconnected form of modern capitalism. This approach to purpose is now gaining regulatory traction. In December 2018, the United Kingdom's "comply or explain" Corporate Governance Code adopted a provision which provides that "the board should establish the company's purpose." This Article takes the United Kingdom's regulatory adoption of mission-purpose as a platform from which we can explore the economic and social benefits of purposeful companies and the legal and non-legal conditions that are necessary to support and nurture such companies. The Article argues that in the absence of purposeful shareholders corporate law must enable companies to construct a zone of insulation which protects its purpose—whatever it may be—from the pressures of immediate shareholder preferences which can compromise mission-purpose. It argues that in jurisdictions where law and market practice prevent the construction of such a zone of insulation, the economic and social benefits of purposeful companies will be unavailable, as mission-purpose disintegrates into the prosaic or a mere marketing device. This claim generates several theoretical and empirical objections, which the Article considers and rejects.